1997
DOI: 10.1159/000106644
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Disease Assessment Scale: The Validation of the Scale in Greece in Elderly Demented Patients and Normal Subjects

Abstract: Introduction: The Alzheimer Disease Assessment Scale (ADAS) is a scale specifically structured for the assessment of the cognitive decline and behavioral disorder seen in Alzheimer disease (AD) patients. Aim of the Study: The validation of ADAS in the Greek population. Material: One hundred and thirty-one subjects took part in the current study. Fifty of them were nondemented subjects (35 normal subjects and 15 suffering from age-associated memory impairment) and 81 demented patients (68 AD patients and 13 vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 15 publications
(15 reference statements)
5
28
1
4
Order By: Relevance
“…In ROC analysis, ADAS-K displayed high diagnostic efficacy (AUC 0.945 for ADAS-K-total, AUC 942 for ADAS-K-cog). The optimal cut-off point 15/16 (sensitivity 90%, specificity 83%) of ADAS-K-cog was similar to that reported from a previous study featuring a Greek version (Tsolaki et al, 1997).…”
Section: Discussionsupporting
confidence: 83%
“…In ROC analysis, ADAS-K displayed high diagnostic efficacy (AUC 0.945 for ADAS-K-total, AUC 942 for ADAS-K-cog). The optimal cut-off point 15/16 (sensitivity 90%, specificity 83%) of ADAS-K-cog was similar to that reported from a previous study featuring a Greek version (Tsolaki et al, 1997).…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, using all 11 items (score range 0-70) and a cut-off (6) score of 12 for AD, the sensitivity was 0.95 and the specificity was 0.97. The high internal consistency, reliability, and validity of the Chinese ADAS-Cog compare favorably with findings based on its version in English [1,2,3,10] or other languages [7,9]. These findings pave the way for its use in AD drug trials and other research studies for Chinese populations.…”
Section: Discriminant Item Analysismentioning
confidence: 52%
“…Previous studies have shown that the cognitive subscale of the ADAS, or ADASCog, had high internal consistency and test-retest reliability [2], was minimally influenced by education and was highly effective in detecting AD and following its progression [3]. By now the ADAS has been translated into Japanese [4], German [5], French [6], Greek [7], Spanish [8], and Italian [9], and it is one of the most popular instruments used for assessing the efficacy of drug treatment of AD [10].…”
Section: Introductionmentioning
confidence: 99%
“…The sample of the study was composed of demented patients with both MID and AD, similarly to previous studies [9,30,37].…”
Section: Methodsmentioning
confidence: 99%
“…In 1997, a Greek version was also validated on 50 nondemented subjects and 81 demented patients with AD and multi-infarct dementia (MID), and the results show that the ADAS cognitive score discriminates perfectly between AD patients and non-demented subjects at the cut-off score of 14 [30]. Versions of ADAS in non-English languages have already been used in Japan [31] and in France [32].…”
Section: Introductionmentioning
confidence: 99%